PERBANDINGAN HASIL BELAJAR DISCOVERY LEARNING BERBASIS PROBLEM SOLVING DAN GROUP INVESTIGATION BERBASIS PROBLEM SOLVING PADA PEMBELAJARAN METODE NUMERIK - Ira Vahlia; Rina Agustina (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
Discovery learning is a learning that involves students in the process of mental activity through a brainstorm, to discuss, and try it yourself, so that children can learn to be independent. Resulting in the discovery-based learning problem solving is to let children discover things on their own and group investigation that emphasizes problem solving based on a debriefing activities and student participation. The classes drawn into the sample, the class as a class given control based discovery learning and problem solving one class another group investigation given learning-based problem solving. Data analysis techniques in this study using Ttes. From the results of this study concluded that: (a) In the first experiment class that implements learning model-based problem solving group investigation obtained average value of learning outcomes at 73.10 while the experimental class II implementing discovery-based learning problem solving obtained average value postest average of 66.55. (b) There are significant differences between the results of student learning in the class that implements the discovery-based learning and problem solving class that implements the learning model based problem solving group investigation. Student results in learning problem solving based group investigation better on the class that implements the model-based discovery learning problem solving.